2008
DOI: 10.1038/sc.2008.66
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of repeated motor and sensory scores at individual myotomes and dermatomes in young persons with complete spinal cord injury

Abstract: Study Design: Prospective repeated measures. Objectives: Evaluate intra-rater agreement of repeated motor and sensory scores at individual spinal levels. Setting: Non-profit pediatric rehabilitation center. Methods: Fifty-eight youth with complete spinal cord injury undergoing two neurological exams. Agreement between exams for each myotome and dermatome was evaluated for four neurological groups: C1-C4 (N ¼ 9); C5-C8 (N ¼ 8); T1-T6 (N ¼ 22); T7-T12 (N ¼ 19). Kappa (k) and weighted k (k w ) coefficients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…An ICC of 1 indicates complete agreement; this occurred only in subjects with complete SCI. These findings may have occurred because those muscles that were scored as a 5 (normal) and 0 (paralyzed) were also included in the results; previous reports 10,17 have shown that agreement of repeated testing of unimpaired and completely paralyzed muscles is usually perfect, and for this reason, previous studies have excluded them from analysis. 5 We choose not to exclude myotomes and dermatomes that were unimpaired and completely paralyzed because this would lead to a variable number of myotomes and dermatomes at each level, potentially, leading to skewed data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An ICC of 1 indicates complete agreement; this occurred only in subjects with complete SCI. These findings may have occurred because those muscles that were scored as a 5 (normal) and 0 (paralyzed) were also included in the results; previous reports 10,17 have shown that agreement of repeated testing of unimpaired and completely paralyzed muscles is usually perfect, and for this reason, previous studies have excluded them from analysis. 5 We choose not to exclude myotomes and dermatomes that were unimpaired and completely paralyzed because this would lead to a variable number of myotomes and dermatomes at each level, potentially, leading to skewed data.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous work, 10 we hypothesized that, regardless of the American Spinal Injury Association Impairment Scale designation, there would be moderate-to-high agreement for motor scores at individual levels for both inter-and intra-rater reliability. Conversely, for incomplete injuries, we expected agreement of sensory scores at individual levels to be moderate-to-high for intra-rater reliability and only moderate for inter-rater reliability.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5 This multicentered study was reviewed and approved by the Institutional Review Boards at participating sites. Written informed consent was obtained from parents or legal guardians of all subjects under the age of 18 years old and participants between ages of 7 and 18 completed informed assents.…”
Section: Methodsmentioning
confidence: 99%
“…8,[11][12][13] It reports on the derivation of a limited dermatome test based on a principal components analysis (PCA) using 726 full sensory exams with 190 children and youth with SCI.…”
Section: T He International Standards For Neurological Classificationmentioning
confidence: 99%